Investigation of Flow Behavior in Minimum Quantity Lubrication Nozzle for End Milling Processes - Najiha, M. S.; M. M., Rahman; A. R., Yusoff; K., Kadirgama (Universiti Malaysia Pahang, 2012)
Minimum quantity lubrication (MQL) is a sustainable manufacturing technique that has replaced conventional flooded lubrication methods and dry machining. In the MQL technique, the lubricant is sprayed onto the friction surfaces through nozzles through small pneumatically-operated pumps. This paper presents an investigation into the flow behavior of the lubricant and air mixture under certain pressures at the tip of a nozzle specially designed for MQL. The nozzle used is an MQL stainless steel nozzle, 6.35 mm in diameter. Computational fluid dynamics is used to determine the flow pattern at the tip of the nozzle where the lubricant and compressed air are mixed to form a mist. The lubricant volume flow is approximately 0.08 ml/cycle of the pump. A transient, pressure-based, three- dimensional analysis is performed with a viscous, realizable k-İ model. The results are obtained in the form of vector plots and flow fields. The flow mixing at the tip of the nozzle is wholly shown through the flow fields and vector plots. This study provides an insight into the flow distribution at the tip of the nozzle for a certain pressure to aid modifications in the design of the nozzle for future MQL studies. It attainable aids to determine the correct pressure for the air jet at the nozzle tip.